2015
DOI: 10.1039/c5cp02663f
|View full text |Cite
|
Sign up to set email alerts
|

Coherent light-driven electron transport through polycyclic aromatic hydrocarbon: laser frequency, field intensity, and polarization angle dependence

Abstract: A laser field is a potential control tool for operating ultrafast electronic devices due to a wide variety of options such as field strength, frequency, and polarization. To investigate these variables upon electron transport through a single-molecule device, we simulate a phenyl-acetylene macrocycle (PAM) within a linear-polarized laser field using single-particle Green's functions combined with the non-Hermitian Floquet theory. In the absence of the laser field, the PAM behaves as a perfect insulator due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 89 publications
(239 reference statements)
0
4
0
Order By: Relevance
“…Electron transport through single molecules attracts general interest since a large diversity of molecules may provide novel applications for next generation electronics. [1][2][3][4] During the last two decades, molecules have been found that can act as passive components such as resistors 5,6 and active components such as transistors, [7][8][9] rectifiers, [10][11][12] and optoelectronic devices, [13][14][15][16] indicating that molecular electronics has the makings of a prototype for modern electronics. To further explore these prospects, integrating individual components together forming intramolecular circuits and logic gates is required.…”
Section: Introductionmentioning
confidence: 99%
“…Electron transport through single molecules attracts general interest since a large diversity of molecules may provide novel applications for next generation electronics. [1][2][3][4] During the last two decades, molecules have been found that can act as passive components such as resistors 5,6 and active components such as transistors, [7][8][9] rectifiers, [10][11][12] and optoelectronic devices, [13][14][15][16] indicating that molecular electronics has the makings of a prototype for modern electronics. To further explore these prospects, integrating individual components together forming intramolecular circuits and logic gates is required.…”
Section: Introductionmentioning
confidence: 99%
“…Coherent electron transport through irradiated molecular junctions has been investigated by several pioneering groups, , and photon-assisted tunnelling is considered a main contribution in the coherent limit. , Within the framework of Floquet-based methods accompanied by a tight-binding model, Tikhonov et al and Keller et al developed a scattering approach in which each Floquet state was treated as an independent transport channel. Lehmann et al derived the current formula from a reduced density matrix formalism in which the coherence between Floquet states was considered.…”
mentioning
confidence: 99%
“…To explore the physical meaning of the shifting in Fig. 4(a)-(c), we analyze it using the Floquet method [53], which has been extensively used in chemical physics [54,55]. Details of the Floquet method can be found in Appendix B.…”
Section: Resultsmentioning
confidence: 99%